Avaliação do repertório verbal inicial em crianças com deficiência auditiva pré-lingual usuárias de implante colclear. - Gaia, Tatiana Francis (2005)
The cochlear implant is a device that allows deaf people to detect surrounding sounds, including the human speech, which are transformed in electric stimulation of the cochlea. This is just the starting point for those who were deprived of audition, especially if the deafness occurred before language acquisition (pre-lingual deafness). After the implant, the person needs to learn (or relearn) to listen, and this is an important research and intervention issue. The goal of this study was to describe the evolution of the listening behavior in pre-lingual implanted children, in a period of time correspondent to the first 26 months after the implant. The analysis consisted of word recognition, figure naming and echoic behavior. In the recognition task, for each dictated word the participants were required to identify the corresponding figure (between three possible figures simultaneously available). On the figure naming task, a figure was shown and the participants were required to pronounce its name. On the echoic behavior required that a dictated word should be repeated by the participants. Twenty words were tested on each evaluation for word recognition, and the same twenty words were tested on the two remaining tasks. A microcomputer presented the participants with the stimuli (so oral-facial clues were avoided), and recorded responses that required selection, spoken words by children were videotaped and transcribed by direct observation. Three successive evaluations were performed with a mean interval of 5 months between them. Pre-training was conducted in order to orient the children on how to do the tasks and use the mouse. The tasks were applied individually, and the data analysis was also performed separately for each participant. The initial evaluation showed intermediate scores on word recognition and low scores or no correct answers on figure naming and echoic behavior. Progressive and substantial increase in word recognition naming and echoic behaviors also improved, but the magnitude of progress was much smaller than that observed in word recognition. In addition to the correct/incorrect criterion of analysis, answers that were close to the vocal emission considered correct (partially correct answers) were also analyzed, and a distinction between wrong answers and no answers at all was made. The evaluation of the partially correct answers was important for the identification of a progressive improvement on the echoic behavior and figure naming performances in which, although the children didn t reach the absolute correct criterion, they showed a systematic progress and attested learning of these important behaviors, which are part of language and whose acquisition is dependent upon audition. A second important observation was the reduced occurrence of no answers in the initial evaluations and the absence of this category of responding in the last evaluation. The improvements observed in the children s behavior are important indictors of learning oral language (comprehension and intelligible speech) after the implant; in the other hand, the gaps observed in their performances strongly suggest the need for educational interventions that aim to accelerate the acquisition of the implant user s repertoires, as well as to refine them, in order to maximize the benefits provided by this device.